A Virtual Reality avatar interaction (VRai) platform to assess residual executive dysfunction in active military personnel with previous mild traumatic brain injury: proof of concept. (3rd October 2017) - Robitaille, Nicolas; Jackson, Philip L.; Hébert, Luc J.; Mercier, Catherine; Bouyer, Laurent J.; Fecteau, Shirley; Richards, Carol L.; McFadyen, Bradford J.
Abstract: Purpose: This proof of concept study tested the ability of a dual task walking protocol using a recently developed avatar-based virtual reality (VR) platform to detect differences between military personnel post mild traumatic brain injury (mTBI) and healthy controls. Methods: The VR platform coordinated motion capture, an interaction and rendering system, and a projection system to present first (participant-controlled) and third person avatars within the context of a specific military patrol scene. A divided attention task was also added. A healthy control group was compared to a group with previous mTBI (both groups comprised of six military personnel) and a repeated measures ANOVA tested for differences between conditions and groups based on recognition errors, walking speed and fluidity and obstacle clearance. Results: The VR platform was well tolerated by both groups. Walking fluidity was degraded for the control group within the more complex navigational dual tasking involving avatars, and appeared greatest in the dual tasking with the interacting avatar. This navigational behaviour was not seen in the mTBI group. Conclusions: The present findings show proof of concept for using avatars, particularly more interactive avatars, to expose differences in executive functioning when applying context-specific protocols (here for the military). Implications for rehabilitation: Virtual reality provides a means to control context-specific factors for assessment and intervention. Adding human interaction and agency through avatars increases the ecologic nature of the virtual environment. Avatars in the present application of the Virtual Reality avatar interaction platform appear to provide a better ability to reveal differences between trained, military personal with and without mTBI.